2018
DOI: 10.1055/a-0650-4820
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signatures of Lithium Treatment: Current Knowledge

Abstract: Lithium (Li) is the key mood stabilizer in the prevention of mood recurrences and suicide in bipolar disorders. However, only one-third of patients become asymptomatic with Li treatment, and to date, no clinical markers can predict this response variability. Li is a multitargeting drug, complicating an understanding of its mechanisms of action. The present article reviews Li's various biological effects, including those obtained in transcriptomic and epigenetic studies, in both humans and animal models. A mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Although Li has not yet been considered to be an essential trace element, it mediates important functions in humans and animals [ 22 , 27 ]. Schrauzer recommended a provisional dietary Li intake of 1000 µg per day [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Li has not yet been considered to be an essential trace element, it mediates important functions in humans and animals [ 22 , 27 ]. Schrauzer recommended a provisional dietary Li intake of 1000 µg per day [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…One soft drink, namely, Acai 28 Black (105 µg Li/L), exhibited Li values comparable to the mean Li values found in mineral water ( Table 5). Although Li has not yet been considered to be an essential trace element, it mediates important functions in humans and animals [22,27]. Schrauzer recommended a provisional dietary Li intake of 1000 µg per day [21].…”
Section: Analysis Of Beveragesmentioning
confidence: 99%
“…Therefore, there is a great need for the tools that would guide the clinicians in selecting a correct treatment strategy. Our data may be useful for understanding the variability of response to lithium in the medicine practice across individuals shown in many works [36,37,59]. We agree that important questions regarding the mechanism of lithium action on anxiety and depression remain open [61] despite much practice in application.…”
Section: B Effects Of Licl On Psychoemotional State Of Animals and Hmentioning
confidence: 58%
“…It was similarly shown that patients with bipolar disorder demonstrate lithium responsiveness of two types: they are good responders or poor responders [41]. Lithium is obviously a multitarget drug, which complicates understanding of its mechanism of action [59]. Lithium as a monotherapy or in combination with other drugs is effective in 60% of chronically treated patients, but response remains heterogeneous, and a large number of patients require a change in therapy after several weeks or months [60].…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal medulla is involved in stress-related disorders which impact mental health conditions including bipolar disorder and other related illnesses (43)(44)(45)(46). Lithium, a widely used drug for the treatment of bipolar disorder (47)(48)(49)(50), modulates sodium and calcium channels of chromaffin cells (51)(52)(53). Regulation of sodium and calcium channels, essential for neurotransmitter secretion, suggested that lithium may modulate neurotransmitter secretion from chromaffin cells.…”
Section: Introductionmentioning
confidence: 99%